A generalized - expansion method for the loaded negative order Korteveg-de Vries equation: A generalized - expansion method for the loaded negative order Korteveg-de Vries equation - Уразбоев, У.У; Хасанов, М. М.; Исмоилов, О.Б. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Keywords : solution, loaded modified negative order Korteveg-de Vries equation, nonlinear equations, expansion method This paper is dedicated to find the solutions of the equation of the loaded negative order Korteveg de Vries equation. It is shown to find the solutions via - expansion method that is one of the most effective way of finding solutions.